Water-energy-food-environment nexus in action: global review of precepts and practice - Shah, Tushaar (Cambridge University Press, 2023)
Using water-energy-food-environment (WEFE) nexus as the prism, this review explores evolution of groundwater governance in Iran, Saudi Arabia, Mexico, China, Bangladesh and India – which together account for two-thirds of the global groundwater-irrigated area. Global discourse has blamed widespread water scarcity squarely on supply-side policymaking and advocated a broader template of water governance instruments. Integrated Water Resources Management (IWRM) presented just such a template – with pricing, participation, rights and entitlements, laws, regulations, and river basin organizations – as additional water governance tools. However, the IWRM template faced disillusionment and pushback in many emerging economies. WEFE nexus, the new paradigm, prioritizes system-level optima over sectoral maxima by harnessing synergies and optimizing trade-offs between food, water, energy, soil, and eco-system sustainability within planetary boundaries. Realizing this vision presents a complex challenge in groundwater governance. Global groundwater economy comprises three sub-economies: (a) diesel-powered unregulated, as in Nepal terai, eastern India, Bangladesh, Pakistan Punjab and Sind, and much of Sub-Saharan Africa, where use-specific energy subsidies are impractical; (b) electricity-powered regulated, as in North America and Europe, where tubewells are authorized, metered and subject to consumption-linked energy charges; and (c) electricity-powered unregulated, as in geographies covered by our review – barring China, Bengal and Bangladesh – where unmeasured electricity subsidies have created a bloated groundwater economy. This last sub-economy represents the heartland of global groundwater malgovernance, least equipped to meet the sustainability challenge. It has an estimated 300 million horsepower of grid-connected electric pumps that are either unauthorized and/or unmetered and/or use free or heavily subsidized or pilfered power for irrigating 50–52 million hectares, nearly half of global groundwater-irrigated area. In (a) and (b), groundwater scarcity inspires water-energy saving behavior via increased energy cost of pumping. In sub-economy (c), users are immune to energy costs and impervious to groundwater depletion. Here, the WEFE nexus has remained blind to the irrigation realpolitik that catalyzes or constrains policy action. We explore why the political costs of rationalizing subsidies are prohibitive and exemplify how a smart transition from fossil to solar energy for pumping may offer an opportunity to turn the perverse WEFE nexus into a virtuous one.